Peran Lingkungan Dalam Memoderasi Penerapan E-Filling Dan Tingkat Kepercayaan Pada Pemerintah Terhadap Kepatuhan Wajib Pajak - Fastha Aulia Pradhani; Juwita Sari (Jurnal Akademi Akuntansi, 2022)
Tax compliance is one of the factors supporting the successful of taxation.  E-filling is one of the applications provided by Directorate General of Taxes to report tax online. The level of public trust in government will be expected to affect tax compliance. External factors such as environment around taxpayers will be expected to influence indirectly tax compliance. Based on the description, this study tries to prove the effect of e-Filling, the level of trust on tax compliance, with the environment as a moderating variable. The population of the study is the employees of Cooperatives & Micro Business Office Sidoarjo who are taxpayers and at least have used e-filling, totalling 65 respondents. The method of the study used PLS-SEM. The results show that e-Filling and environment has a significant positive effect on tax compliance, but not for the level of trust. The environment moderates the relationship between e-Filling on tax compliance, but there is no moderating relationship between the level of trust and tax compliance.